Substrate Specificity of the Escherichia coli Outer Membrane Protease OmpT - McCarter, John D. (American Society for Microbiology, 2004)
OmpT is a surface protease of gram-negative bacteria that has been shown to cleave antimicrobial peptides, activate human plasminogen, and degrade some recombinant heterologous proteins. We have analyzed the substrate specificity of OmpT by two complementary substrate filamentous phage display methods: (i) in situ cleavage of phage that display protease-susceptible peptides by Escherichia coli expressing OmpT and (ii) in vitro cleavage of phage-displayed peptides using purified enzyme. Consistent with previous reports, OmpT was found to exhibit a virtual requirement for Arg in the P1 position and a slightly less stringent preference for this residue in the P1′ position (P1 and P1′ are the residues immediately prior to and following the scissile bond). Lys, Gly, and Val were also found in the P1′ position. The most common residues in the P2′ position were Val or Ala, and the P3 and P4 positions exhibited a preference for Trp or Arg. Synthetic peptides based upon sequences selected by bacteriophage display were cleaved very efficiently, with k(cat)/K(m) values up to 7.3 × 10(6) M(−1) s(−1). In contrast, a peptide corresponding to the cleavage site of human plasminogen was hydrolyzed with a k(cat)/K(m) almost 10(6)-fold lower. Overall, the results presented in this work indicate that in addition to the P1 and P1′ positions, additional amino acids within a six-residue window (between P4 and P2′) contribute to the binding of substrate polypeptides to the OmpT binding site.